Sports Orthopedics - Kibele A; Claußen L; Eckardt N (Dynamic Media Sales Verlag, 2021)
Using resistance training on unstable supports or with instability devices athletes aim to prepare their neuromuscular system for sudden and unforeseen impairments in equilibrium impeded by the environment or through sports partners. In contrast to athletes, older adults aim to avoid such situations impeded by instability to reduce a possible risk of falling.The goal of this review is to outline the specific benefits of resistance training on unstable supports or with instability devices, denote as metastability resistance training (MRT), in older adults while extending knowledge of past reviews in this field.Existing studies comparing MRT to traditional resistance training (RT) on stable surfaces are reviewed and summarized. Our review shows that MRT: a) is safe for the older adult when properly introduced and supervised; b) requires smaller training loads and stresses larger articular areas while providing similar or larger gains in strength as traditional RT on stable surfaces; c) provides extended gains in functional mobility, balance, and power; d) offers a strengthening of stabilizer muscles whose strength loss is assumed to facilitate falls; e) stabilizes gait performance and, thus, reduces the risk of falls; f) improves cognitive performance reducing reductions the fear of falling and improves executive functions.Moreover, MRT was found to be particularly beneficial for Parkinsons disease patients. Hence, MRT could be a very useful tool to complement the physical conditioning of older adults.Key Words: Instability Resistance Training, Metastability, Fall Prevention, Fear of Falling